Seasonal and post-rainfall dynamics of soil CO 2 efflux in wheat and peanut fields - Chayawat C. (2014)
It is crucial to understand the effect of rainfall on soil CO 2 efflux and the factors that control efflux. This paper investigates the influence of rainfall events on soil CO 2 efflux from wheat and peanut fields by using high-frequency soil gradient efflux method and long term automated soil chamber measurements. Results show soil CO 2 efflux decreased during and immediately after rainfall events, which was related to reduce gaseous diffusivity as a response. A few hours after rainfall, a significant increase in soil CO 2 efflux was observed, the increased rates of soil CO 2 efflux were different among the growth stages of peanut. A significant correlation between soil water content and soil CO 2 efflux after rainfall was found, suggesting that soil water content has consequence for short-term losses of soil CO 2 efflux after rainfall. The present study suggests that high-frequency soil CO 2 efflux measurements should be made to capture large pulses in CO 2 emissions to adequately model carbon-water cycling from agricultural soils to the atmosphere.